Challenges and Existence of the Mekongga Local Language as a Media for Preserving Local Wisdom - ., Kadaruddin; Baso, Yusring Sanusi; ., Gusnawaty; Hasjim, Munira; Hasyim, Muhammad (International Journal of Membrane Science and Technology, 2023)
The Mekongga local language of Indonesia is an essential part of this country’s cultural variety. Unfortunately, the number of speakers of the local Mekongga languages is decreasing. The Mekongga local language, like other local languages in Indonesia, is on the verge of extinction due to a declining number of speakers. Therefore, preserving the Mekongga local language is critical in order to preserve local wisdom and the local community’s cultural identity. This research aims to describe the maintenance function of the Mekongga local language in the Wundulako Sub-district, Kolaka Regency, Southeast Sulawesi. The quantitative descriptive approach was used in this research, with research subjects consisting of adolescents and adults who were native speakers of the Mekongga language. The data was collected using a closed questionnaire and analyzed using a percentage descriptive technique. The research’s findings show that the speaking community’s attitude toward maintaining the Mekongga local language is positive, with an average of 76.23. However, there are still concerns about the potential extinction of the Mekongga local languages, especially amid the increasing challenges of globalization and modernization. Therefore, more optimal and concrete efforts are needed to preserve the local Mekongga language. These findings provide important implications for development policies directed at maintaining the Mekongga local language and local wisdom inherited from the past. This implication can positively contribute to the development of culture in Indonesia as a whole. This research can also significantly contribute to further research related to maintaining local languages and local wisdom in Indonesia.